Comparison of Throat Washings, Nasopharyngeal Swabs and Oropharyngeal Swabs for Detection of SARS-CoV-2 - Hitzenbichler, Florian (Viruses, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) RNA is detected by reverse-transcription quantitative real-time PCR (RT-qPCR) from respiratory specimens. This study compares throat washings (TW), nasopharyngeal swabs (NS) and oropharyngeal swabs (OS). A total of 102 samples from 34 adult patients with confirmed SARS-CoV-2 infection were analysed by RT-qPCR with absolute quantification. The median concentrations and diagnostic sensitivities were [Formula: see text] copies/mL, 85% (NS), [Formula: see text] , 79% (OS) and [Formula: see text] , 85% (TW). Concentration differences were significant between NS and TW (P = 0.019). Saliva (SA) was available from 21 patients (median [Formula: see text]). OS and TW can be considered for SARS-CoV-2 diagnostics, although with slightly lower concentrations.